SegmentShield: Exploiting Segmentation Hardware for Protecting against Buffer Overflow Attacks - Shinagawa, T. (2006 25th IEEE Symposium on Reliable Distributed Systems (SRDS'06), 2006)
This paper presents a strong and efficient scheme for protecting against buffer overflow attacks. The basic approach of this scheme is pointer copying: copies of code pointers are stored in a safe memory area to detect and prevent the manipulation of code pointers. In order to protect the copied code pointers from data-pointer modification attacks, this scheme exploits the segmentation hardware of IA-32 (Intel x86) processors. This scheme provides as strong protection as write-protecting the memory area via system calls. On the other hand, this scheme involves a modest overhead because copying a code pointer requires only a few user-level instructions and there is no penalty of entering the kernel. The experimental results show that the performance overhead in OpenSSL ranges from 0.9% to 4.3%